(untitled) (Ameghiniana, 2026)
New graptolite faunas from the matrix of the Rinconada Formation at the La Rinconada section, Eastern Precordillera of San Juan (Argentina), are documented. A stratigraphic succession of 375.6 m initiated in a faulted zone was studied in the southeastern part of the outcrops, yielding 12 fossiliferous levels. Lower layers contain an assemblage dominated by Saetograptus argentinus argentinus and Uncinatograptus? sp., associated with cf. Neodiversograptus. Higher levels include Bohemograptus bohemicus, Lobograptus progenitor, Pristiograptus frequens, and Prolinograptus packhami. The upper strata are almost exclusively composed of S. a. argentinus and Saetograptus rinconadensis sp. nov., with a unique occurrence of Lobograptus sp. cf. L. scanicus and Uncinatograptus? sp. Assemblages including Saetograptus, Uncinatograptus?, and possibly Neodiversograptus indicate an early Gorstian age, equivalent to the Neodiversograptus nilssoni Zone. Upwards, the occurrence of the index species L. progenitor allows recognition of the homonymous biozone. Upper assemblages are tentatively assigned to the upper Gorstian L. scanicus Zone or equivalent levels, while the highest levels may reach the lowermost Ludfordian. Accordingly, the new species would have an upper Gorstian to lowermost Ludfordian age. The upper levels exhibit moderate to strong graptolite colony alignment, indicating a WSW (246°) paleocurrent direction that coincides with sedimentary structures and antecedents. This study adjusts Silurian biostratigraphy in Argentina, enabling more accurate regional and global correlations, and expanding knowledge of Ludlow graptolites in South America.